Empirical user studies inform the design of an e-notetaking and information assimilation system for students in higher education - Reimer, Yolanda Jacobs; Brimhall, Erin; Cao, Chen; O’Reilly, Kevin (Computers and education, 2009)
The research presented in this paper reaches towards a better theoretical understanding of how students in higher education currently take notes, how this process is evolving in the digital age to include information assimilation, and the kinds of support students need to be successful with their changing academic tasks. To gain insight into these questions, we triangulated three major and distinct user studies. First we interviewed 70 university students from various disciplines across campus, and we administered questionnaires to these same students, receiving back a total of 68. Our second study was based on participant observation whereby we “shadowed” 32 university students for 2–3 h each as they went about their normal academic business around campus. Lastly, we conducted a broader-based questionnaire with 280 students from a wider campus demographic than our first survey. We sought a diverse population for our research, and were able to include students from the disciplines of Business, English, Computer Science, Chemistry, Psychology, Pharmacy and Biology in one or more of the studies. We discovered how closely students are connected to technology and how they are adapting to changing expectations, current issues they have completing their academic tasks, how they view traditional notetaking versus electronic notetaking, and evidence that they are engaging more and more in the process of information assimilation. From these results, we conclude that students in higher education might accomplish certain tasks more effectively and efficiently with a well-designed software system that provides access to a centralized set of notes from different locations on campus and beyond. After identifying functional requirements for the system we envision, we preview our initial low-fidelity prototypes, and discuss feedback we gathered on these designs from a set of user focus groups.